Trends in the use of induction of labor by methods and indications: A population‐based study - Samia Aziz; Fiona Bruinsma; Kara Blackburn; Caroline S. E. Homer; Joshua P. Vogel (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Induction of labor is a widely used obstetric intervention, with rates increasing globally. In Australia in 2022, over one‐third of women gave birth following the induction of labor. Though the rate of induction has increased, changes in methods and indications for induction have not been analyzed for the state of Victoria. This study aims to analyze these trends in Victoria, Australia. Material and Methods A retrospective cohort study was conducted using de‐identified data from the Victorian Perinatal Data Collection (VPDC) that includes all births statewide of at least 28 completed weeks' gestation from 2012 to 2020. The study analyzed trends in the onset of labor, methods used, and indications for induction over the study period, using descriptive statistics and average annual percentage change. Results A total of 701 324 births occurred during the study period, of which 223 672 (31.9%) were inductions. Induction of labor rates increased significantly from 25.4% in 2012 to 37.7% in 2020, with a notable rise at 38 and 39 weeks' gestation. Significant changes were observed in induction methods—the use of combination methods, particularly balloon catheter followed by pharmacological agents, increased, while the use of a standalone method declined. The findings suggest that gestational diabetes and fetal indications were major drivers of induction in recent years. Conclusions Labor induction practices in Victoria have changed significantly, reflecting shifts in clinical practices and changes in health profiles of pregnant women. Further research is needed to investigate the rising use of induction at early term gestation and the role of maternal preferences in driving induction in Victoria.